2017
DOI: 10.1039/c6ay03309a
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a tailorable and PCR-free detection of Enterococcus DNA isolated from soil samples

Abstract: Bacteria detection is crucial for water and environmental monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…20 While DNA bacteria sensors offer flexibility in targeting genetic sequences in the cells, it requires additional steps to lyse the cell and make the DNA targets available for biosensors. 21 Antibody and antimicrobial peptide-based biosensors, which are highly specific, can detect cells without lysis steps. 22 Kraatz et al have shown how a ferrocene moiety could be used in constructing a label-free electrochemical sensor for detecting E. coli O157:H7 cells down to 10 3 CFU/mL.…”
Section: Introductionmentioning
confidence: 99%
“…20 While DNA bacteria sensors offer flexibility in targeting genetic sequences in the cells, it requires additional steps to lyse the cell and make the DNA targets available for biosensors. 21 Antibody and antimicrobial peptide-based biosensors, which are highly specific, can detect cells without lysis steps. 22 Kraatz et al have shown how a ferrocene moiety could be used in constructing a label-free electrochemical sensor for detecting E. coli O157:H7 cells down to 10 3 CFU/mL.…”
Section: Introductionmentioning
confidence: 99%